Students' Modelling in Learning The Concept of Speed - Khikmiyah, Fatimatul; Lukito, Agung; Patahudin, Sitti Maesuri (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
Previous researchs shows that speed is one of the most difficult in the upper grades of primary school. It is because students must take into consideration of two variables; distance and time. Nevertheless, Indonesian students usually learn this concept as a transmission subject and teacher more emphasizes on formal mathematics in which the concept of speed given as distance by time rigorously. A sequence of learning activities with toy cars context was designed based on students' development and Realistic Mathematics Education (RME) principles which are guided reinvention, didactical phenomenology and emergent modelling. Using their own models, students are able to explain a proportion among distance and time in speed as well the relationship of it. Keywords: The concept of speed, design research, Toy cars, context, ratio tables' model